Thermal properties of doubly reinforced fiberglass/epoxy composites with graphene nanoplatelets, graphene oxide and reduced-graphene oxide. (1st May 2019) - Rafiee, M.; Nitzsche, F.; Laliberte, J.; Hind, S.; Robitaille, F.; Labrosse, M.R.
Abstract: A novel manufacturing method based on Vacuum Assisted Resin Transfer Molding (VARTM) was devised to incorporate carbon nanoparticles for the enhancement of thermal properties of multiscale laminates. Several graphene-based nanomaterials including graphene oxide (GO), reduced graphene oxide (rGO), graphene nanoplatelets (GNPs) and multi-walled carbon nanotubes (MWCNTs) were used to modify the epoxy matrix and the surface of glass fibers. The thermal, rheological and morphological properties of the resulting glass fiber-reinforced multiscale composites were investigated. The thermal properties of the epoxy/nanoparticle composites were studied through thermal conductivity measurements, differential scanning calorimetry (DSC) and thermo-gravimetric analysis (TGA). The thermal characterization results showed that the introduction of GNPs, GO, rGO, and MWCNTs enhanced thermal conductivity. Compared with the neat epoxy/fiberglass composite control results, improvement in thermal conductivity of fiberglass/epoxy modified with MWCNTs 0.3%, GNPs 1%, GO 2% and rGO 0.042% were 8.8%, 12.6%, 8.2% and 4.1%, respectively. It was concluded that for the same volume fraction of nanoparticles, the thermal conductivity improvement in graphene nanoplatelets-modified composites is more pronounced compared with other nanoparticles. A better dispersion of nanoparticles and a better interfacial interaction between nanoparticles and epoxy are essential in enhancing the thermal conductivity of nanocomposite materials.